ANALYSIS OF ATTITUDES TO EDUCATIONAL REFORMS IN UKRAINE OF PHYSICAL EDUCATION TEACHERS AND PRIMARY EDUCATION TEACHERS - Moskalenko, Natalia; Bodnar, Ivanna; Sorokolit, Nataliya; Rymar, Olga; Solovey, Alla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Questions, connected with conduction educational reforms on the modern stage in Ukraine, are discovered in this article. Those changes are connected with desire of Ukrainian society to join European society and to sigh Association with European Union. The educational reform is implemented in primary school. The goal is to find out and analyze physical education teachers’ and primary school teachers’ opinion about implementation educational changes on the present stage in Ukraine.In due to realize such goal we applied literature sources analysis and questionnaire. The questions were answered by 100 physical education teachers and 104 primary school teachers from Lviv region. We have discovered opinion of physical education teachers and primary school teachers is common. The highest level of support got: opportunity to choose and create educational program in terms of educational standards (82% of physical education teachers, 78,9% of primary education teachers), providing different forms of elementary education (76% and 73,1% respectively), applying game methods in studying in elementary school (72% and 69,23% respectively). We have noticed difference in teachers’ attitude towards verbal evaluation of pupils during physical education lessons, progressive forms of retraining and teachers’ independent attestation. Teachers do not support 12-years studying period and implementing the inclusion.